Pengaruh Pendidikan Kesehatan Kanker Serviks Terhadap Motivasi Deteksi Dini Kanker Serviks Pada Perawat Di Rumah Sakit Kanker Dharmais - Novita Sariayu S; Yuni Susilowati; Cicirosnita J.Idu (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Examination results at Dharmais Hospital found cervical cancer out of 1640, 77 of them died. One of the prevention efforts is to carry out regular pap smear examinations, but based on available data every year the motivation of female nurses to carry out pap smear examinations has decreased. In order to increase the awareness of nurses about the importance of early detection, health education can be given related to early detection of cervical cancer. To determine the effect of cervical cancer health education on the motivation for early detection of cervical cancer in nurses at the Dharmais Cancer Hospital Jakarta in 2022. Pre-experimental design with a one group pretest posttest design. The sample size for this study was about 155 married nurses using a purposive sampling technique. Data analysis using the Wilcoxon test. Motivation for early detection of cervical cancer in nurses before being given cervical cancer health education was mostly in the low category 65.2%, afterward most were in the high category 88.4% . With a p value of 0.001, the analysis's results show that nurses' motivation to do early cervical cancer detection is affected by health education the about cancer. There is an influence of cervical cancer health education on the motivation for early detection of cervical cancer in nurses.